PENGARUH KOMPENSASI FINANSIAL DAN KOMPENSASI NONFINANSIAL TERHADAP KINERJA KARYAWAN DI KOPERASI RAUNG TALKANDANG KABUPATEN SITUBONDO - Farida Hanum; Vita Novianti; Mohammad Fahrur Rozi (ACTON, 2017)
The purpose of this study is to determine the effect of financial and nonfinancial compensation on employee performance in Cooperative Raung Talkandang Situbondo. Quantitative research method with a sample of 30 people using total sampling technique. The method of data analysis using validity test, and reliability test while to test the hypothesis in this research can use multiple linear regression analysis, partial test (t test), simultaneous test (F test) assisted SPSS 22.0 for windows. The financial compensation variable has a positive influence of 3,538. Meanwhile, the value at the ttable distribution of 5% or 0.05 of 1.70329, then thitung 3.538> ttabel 1.70329. It is also reinforced by a significant value of 0.001 smaller than the Sig value. 0.05 means that financial compensation variables significantly influence employee performance. While the value of t count for this non financial financial compensation is 2,417. Meanwhile the value at the ttable distribution of 5% or 0.05 then tcount 2.417> ttabel 1.70329. Means that non-financial compensation variable has a positive influence. It is also reinforced with a significant value of 0.023 less than the Sig value. 0.05 means that the non-financial compensation variable significantly affects employee performance.